a Gender Trouble Einar Wegener in David Ebershoff’s The Danish Girl - ahmad zakaria (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
There are some cases of gender that cannot be explained with common sense, like someone who was born with two sexes (intersex), a man who loves to have sex with a man, a male who performs female activities, and even a man who wants to transforms his sex to be a female sex. It shows a point that gender is troubling. It also shows a point that gender can be changed. Among the cases what happens to Einar or Lily in David Ebershoff’s The Danish Girl. David Ebershoff’s The Danish Girl sets in Copenhagen, Denmark. It tells Einar Wegener as a happily married man. He is married to Gerda Wegener. The couple are painters. Einar paints mostly landscapes and Gerda paints mostly portraits of famous people. One day, Einar replaces Gerda’s model, Anna Fonsmark, to be painted. Gerda requests Einar to dress like a woman, makeup and so on. Here, Einar pretends to become Lili. In this Lili’s image mode, Einar feels that Lili is the real of himself. In this internal situation, Einar is trapped in a complex conflict between himself as Einar and himself as Lili. Of course, Einar represents male gender and Lili represents female gender. Those are parts of himself. At that moment, Einar performs double gender. He performs Einar as a man and performs Lili as a woman. Both are performed in a single body. By the main course in the novel, the most cases reveal the story of a man with two genders, male and female. The main character has the problem of gender in his body. He lives with male body, but unconsciously he also reveals his female part living inside. Because Einar/Lili lives in common society, he finally faces conflicts such as feeling isolation from the society and feeling strange of himself. This anxiety gets him/her to do extreme thing. It is genital operations. Einar/Lili indirectly implies problem of gender. It also explains that gender is not fixed, stable, and absolute. Einar/Lili has to fight against him/herself and the society. He was born with penis and he was constructed with male attributes. He just followed and obeyed what was asked to be man, like how to walk, to dress, and so on. But, in a moment, when he knew his lost part, he could not get away. It was Lili’s side in his body that he never knew before. This revelation and decision to be Lili explains that gender is not stable. Einar just performed to in male gender while he had another side of Lili that drove him in female gender. Besides fighting against him/herself inside, he also fights against society with its gender trouble.